Agricultural trade liberalisation, agricultural total factor productivity growth and food security in Africa. Issue 3 (3rd July 2022) - Sunge, Regret; Ngepah, Nicholas
ABSTRACT: The study draws inference on the impact of agricultural trade openness, total factor productivity (TFP) growth, and domestic agriculture support on food security in Africa. To retain estimates efficiency and consistency in the presence of complex error terms, we employed the Panel-Corrected-Standard-Error (PCSE) estimator on panel data spanning 2005–2016 for 13 African countries. Results suggest that agricultural trade liberalisation and TFP have significant and favourable effects. Moreover, we find that reducing agricultural support beyond distortion-free levels enhances food security. Further to trade openness, we call for export growth-oriented domestic support anchored on agricultural human-capital development, innovation, and research and development.